Conservation status of the threatened Iberian Peninsula narrow endemic Antirrhinum lopesianum Rothm. (Scrophulariaceae) - Bernardos, Sónia (2011)
Antirrhinum lopesianum Rothm. is a narrow endemic of the Lusitan Duriensean biogeographical sector (central western Spain and north-eastern Portugal). The species is listed as threatened in several Spanish documents, although it does not figure as such in any Portuguese document. This paper provides a detailed study of its distribution, estimates of the sizes of its populations, the threats it faces, and its current conservation status. The total number of individuals thought to exist is only 768, distributed along the valley of the River Duero on the Spanish – Portuguese border (562, 71.2%), and in the Portuguese Sabor River valley (206, 26.8%). The main threat to the species is loss of habitat: about one third of the Iberian populations can be considered threatened; one population containing 37.6% of all these plants (289) is severely threatened. To determine the Area of Occupancy and the Extent of Occurrence, an exhaustive bibliographical survey was carried out, and herbarium specimens deposited in several institutions were revised. It is, therefore, classifiable as Critically Endangered in Portugal and Endangered in Spain